The Role of Religious Authorities in Renewing Sharia Controls: An Analytical Study in Light of Contemporary Developments and Calamities - Galal Ali Mohammed (Journal of Scientific and Human Dimensions, 2025)
This analytical study examines the role of Religious Authorities in renewing Sharia Controls to keep pace with local and global developments and calamities. The research’s importance lies in addressing the phenomenon of intellectual stagnation (al-Jumud al-Fikri), conformism, and the rejection of differing opinions, which results from disabling the use of reason. The study aims to renounce this stagnation and define the concepts of Religious Authority, Renewal, and Sharia Controls. The researcher defines Religious Authority as: an authorized body to which the Muslim community refers for the jurisprudence of their beliefs, conduct, and transactions. Renewal (Tajdid) is defined as: developing understandings and perceptions so that their fruits appear on the actions (Jawareh) in line with the lived reality and its developments. Sharia Controls are defined as: a set of clear and binding principles and rulings that guide and regulate the course of a Muslim’s life. The research affirms the legitimacy of Renewal, clarifying that it is not achieved by changing the Sharia texts (Qur’an and Sunnah), but by formulating the principles of scrutiny into the evidence and developing methods for inferring rulings and controls to suit the variables. The renewer is required to meet the same conditions as the Mujtahid, including comprehensive knowledge of language, Usul al-Fiqh (principles of jurisprudence), and Maqasid al-Sharia (objectives of Sharia). The study concludes that developing and renewing Sharia Controls is the direct role entrusted to Religious Authorities.